Arabic manuscripts a vademecum for readers - Gacek, Adam (Handbuch der Orientalistik. Nahe und der Mittlere Osten ;, 2009)
The main sequence is comprised of approximately 200 entries dealing with almost all aspects of Arabic manuscript studies (codicology and paleography); includes appendices covering abbreviations, letterforms, sūrah-headings, major reference works, and a guide to the description of manuscripts, as well as charts of major historical periods and dynasties.